Fetal-Maternal Interactions in the Synepitheliochorial Placenta Using the eGFP Cloned Cattle Model - Pereira, Flavia Thomaz Verechia; Oliveira, Lilian J.; Barreto, Rodrigo da Silva Nunes; Mess, Andrea; Perecin, Felipe; Bressan, Fabiana Fernandes; Mesquita, Ligia Garcia; Miglino, Maria Angelica; Pimentel, José Rodrigo Valim; Neto, Paulo Fantinato; Meirelles, Flávio Vieira (Public Library of Science (PLoS), 2013)
Background: To investigate mechanisms of fetal-maternal cell interactions in the bovine placenta, we developed a model of transgenic enhanced Green Fluorescent Protein (t-eGFP) expressing bovine embryos produced by nuclear transfer (NT) to assess the distribution of fetal-derived products in the bovine placenta. In addition, we searched for male specific DNA in the blood of females carrying in vitro produced male embryos. Our hypothesis is that the bovine placenta is more permeable to fetal-derived products than described elsewhere. Methodology/Principal Findings: Samples of placentomes, chorion, endometrium, maternal peripheral blood leukocytes and blood plasma were collected during early gestation and processed for nested-PCR for eGFP and testis-specific Y-encoded protein (TSPY), western blotting and immunohistochemistry for eGFP detection, as well as transmission electron microscopy to verify the level of interaction between maternal and fetal cells. TSPY and eGFP DNA were present in the blood of cows carrying male pregnancies at day 60 of pregnancy. Protein and mRNA of eGFP were observed in the trophoblast and uterine tissues. In the placentomes, the protein expression was weak in the syncytial regions, but intense in neighboring cells on both sides of the fetal-maternal interface. Ultrastructurally, our samples from t-eGFP expressing NT pregnancies showed to be normal, such as the presence of interdigitating structures between fetal and maternal cells. In addition, channels-like structures were present in the trophoblast cells. Conclusions/Significance: Data suggested that there is a delivery of fetal contents to the maternal system on both systemic and local levels that involved nuclear acids and proteins. It not clear the mechanisms involved in the transfer of fetal-derived molecules to the maternal system. This delivery may occur through nonclassical protein secretion; throughout transtrophoblastic-like channels and/or by apoptotic processes previously described. In conclusion, the bovine synepitheliochorial placenta displays an intimate fetal-maternal interaction, similar to other placental types for instance human and mouse. © 2013 Pereira et al.
Keywords: cell protein; DNA; enhanced green fluorescent protein; messenger RNA; testis specific Y encoded protein; unclassified drug; animal cell; animal tissue; blood sampling; cattle; cell interaction; cell nucleus transplantation; cell structure; controlled study; embryo; female; fetus cell; gene expression; gene identification; gene location; immunohistochemistry; immunolocalization; in vitro study; maternal blood; microscopy; molecular cloning; molecular dynamics; nonhuman; placenta; polymerase chain reaction; protein determination; protein expression; protein localization; transgene; transmission electron microscopy; trophoblast; Western blotting